Attenuated Total Reflection Fourier Transform Infrared (ATR FT-IR) Spectroscopy Sensitivity to the Thermal Decay of Bone Collagen. Issue 1 (January 2023) - Thomas, Brian; Anderson, Kevin; De Silva, Imesha; Verbeck, Guido; Taylor, Stephen
The analysis of collagen stability is of interest in forensics, archaeology, and molecular paleontology. Collagen decay rates are often measured by thermal kinetic studies that employ liquid chromatography mass spectrometry (LC-MS) to assay collagen quantities. However, these kinetic studies generally focus on measuring the decreasing levels of collagen instead of an exact molecular concentration of each sample. Thus, attenuated total reflection Fourier transform infrared (ATR FT-IR) spectroscopy can offer a simpler and less expensive alternative to LC-MS. The application of a new protocol to determine decreasing amounts of bone collagen in artificially decayed porcine and bovine bone was assessed. The protocol uses a forensic application of ATR FT-IR spectroscopy on size-restricted bone powder from three uniformly high temperature conditions. Also, for the first time, collagen-specific second-harmonic generation (SHG) imaging was also applied to artificially aged bone to add an independent, qualitative perspective to parallel FT-IR assessments. SHG images and ATR FT-IR spectra together reveal the same orderly bone collagen decay as found in previous thermal kinetic studies. Resulting Arrhenius plots with r 2 values > 0.95 suggest that the ATR FT-IR-based protocol has potential as a precise and simple tool for measuring bone collagen decay rates. The results are significant for applications of thermal kinetic studies, and our protocol can serve as an inexpensive, precise, and pragmatic means of evaluating bone collagen stability within an array of conditions. Graphical Abstract